Highly Fluorescent, π‐Extended Indenopyrido[2, 1‐a]isoindolone Derivatives Prepared by a Palladium‐Catalysed Cascade Reaction. Issue 12 (13th March 2013) - el abidine Chamas, Zein; Marchi, Enrico; Modelli, Alberto; Fort, Yves; Ceroni, Paola; Mamane, Victor
Abstract: A new family of heterocyclic pentacyclic compounds have been prepared by a cascade reaction involving 2, 5‐dihalopyridines and (2‐formylphenyl)boronic acids. Most of the compounds exhibit high quantum yields of fluorescence in dichloromethane. In some cases, small changes in the substitution pattern caused fluorescence quenching. To rationalize this effect, a detailed photophysical study combined with electrochemical and computational studies was performed on four representative derivatives. It appears that the fluorescence quenching is caused by a thermally activated non‐radiative deactivation process that can be prevented in a rigid matrix such as ethanol at 77 K or a PMMA polymer. Abstract : Highly fluorescent pentacyclic compounds have been synthesized by a palladium‐catalysed cascade reaction. The fluorescence quantum yields and lifetimes of the luminescent excited states of these compounds are strongly influenced by the electronic nature and position of the substituents. These effects have been rationalized on the basis of photophysical, electrochemical and computational studies.